Pemasaran Pada Era Globalisasi - Situmorang, James Rianto (Business Administration Study Program - Universitas Katolik Parahyangan, 2012)
In the era of globalization many companies choose a global target market. The com-panies are going to carry out the global marketing activities or marketing strategiesthat match the conditions of the world today. Currently there are almost borderlessworld with the advent of the internet and the free trade blocks as a result of global-ization in economics and business. Internet is very easily done by companies aroundthe world, and the free trade makes it easy for companies to market their productsto various countries around the world. Global marketing is not only done by largecorporations, but also can be done by Small and Medium Enterprises (SMEs).Keywords: Globalization, marketing, global marketing, strategy